Digital long‐term topoclimate surfaces of the Pyrenees mountain range for the period 1950–2012. (19th November 2018) - Batalla, Meritxell; Ninyerola, Miquel; Catalan, Jordi
Abstract : Long‐term climate data accounting for high‐spatial variability and detailed topographic effects are crucial for research and management in complex terrains such as mountain ranges. Here, we introduce the Pyrenean Digital Climate Atlas based on data from around 400 weather stations located across the range during the 1950–2012 period. Average monthly, seasonal, and annual temporal resolutions are provided for 30‐m spatial resolution surfaces. Local heterogeneity was considered, integrating meteorological station data, high‐quality terrain information (altitude, latitude, distance to the sea, and solar potential radiation) and multivariate regression modelling in a Geographical Information System. Climate surfaces of air temperature (minimum, maximum, and mean) and precipitation were obtained and used to derive maps of bioclimatic interest such as potential evapotranspiration, water availability, and growing degree‐days. Metadata are provided in XML standard format (ISO 19139) with all the usual fields and quality indicators for each map, with an RMSE ranging from 0.7 to 1.2°C and 11 to 15 mm for air temperature and precipitation maps respectively. The Atlas is available in GeoTIFF format at the ZENODO repository. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available atDOI 10.5281/zenodo .1186639. Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .